KONSEP IMPLEMENTASI MERDEKA BELAJAR DI SEKOLAH DASAR MENURUT PANDANGAN FILSAFAT KONTRUKTIVISME - Rati Syafiana Putri; Desyandri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
ABSTRACTMerdeka Belajar can be understood as the implementation of a program that promotes pleasant situations in the learning process. The purpose of this study is about the concept of implementing Merdeka Belajar in elementary schools according to the philosophy of constructivism. The method used to compile this article is a literature study. This literature review is a reference survey of books, articles. The concept of education through Merdeka Belajar in the perspective of progressive philosophy has the same concept and the same goals, which require changes that are much better in the administration of education. The philosophy of progressivism argues that students must be progressive or advanced, act constructively, think critically, and be active. An important element of the Merdeka Belajar program at the elementary school level is strengthening the basic skills of understanding logistics and learning by strengthening the profile of Pancasila students.